Influence of irradiation treatment on sensing performances of screen-printed electrodes aimed for doxorubicin monitoring - Perica Paunović; Iva Dimitrievska; Marija Katerina Paunović; Marija Mitevska; Anita Grozdanov (Journal of Electrochemical Science and Engineering)
The subject of study is the development of nanosensors based on carbon nanotubes (CNTs) and polyaniline (PANI) aimed at effective detection and monitoring of doxorubicin - a chemotherapy drug used in the treatment of different types of cancer. The main goal is the design of nanosensors that provide precise and reliable detection and monitoring of doxorubicin, providing an effective approach to monitor drug levels during treatment. The research was carried out on the screen-printed electrodes (SPE) with a working electrode of commercial CNTs and PANI and their modification by irradiation with electron irradiation (50 kGy). The structural changes resulting from the e-beam irradiation were observed by scanning electron microscopy, Raman and FTIR spectroscopy, and thermogravimetric analysis. An electrochemical study employing cyclic voltammetry was done to characterize and test the performance of the nanosensors. Modification with electron irradiation was shown as an effective approach to improve the sensing characteristics of the studied SPE, resulting in a lower limit of detection for the modification. The irradiated SPEs exhibit a limit of detection of 12.674 µmol L⁻¹ for the modified multi-walled CNT (MWCNT) electrode and 12.712 µmol L⁻¹ for the modified PANI electrode, compared to 12.773 µmol L⁻¹ for the MWCNT and 12.712 µmol L⁻¹ for the PANI commercial electrodes.